2003
DOI: 10.1046/j.1462-5822.2003.00329.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of host-pathogen interactions using Listeria monocytogenes and Drosophila melanogaster

Abstract: SummaryThe facultative intracellular bacterial pathogen Listeria monocytogenes is capable of replicating within a broad range of host cell types and host species. We report here the establishment of the fruit fly Drosophila melanogaster as a new model host for the exploration of L. monocytogenes pathogenesis and host response to infection. Listeria monocytogenes was capable of establishing lethal infections in adult fruit flies and larvae with extensive bacterial replication occurring before host death. Bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
141
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(151 citation statements)
references
References 40 publications
8
141
0
2
Order By: Relevance
“…Insects have been employed to assess the relative pathogenicity of bacteria [19], fungi [20] and parasites [21] and positive correlations with results from murine studies have been demonstrated in C. albicans [22] and Pseudomonas aeruginosa [23].…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…Insects have been employed to assess the relative pathogenicity of bacteria [19], fungi [20] and parasites [21] and positive correlations with results from murine studies have been demonstrated in C. albicans [22] and Pseudomonas aeruginosa [23].…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…The insect immune response bears a number of similarities to the innate immune response of mammals and as a result various insects have been utilised for assessing the pathogenicity of bacterial [2] and fungal isolates [3] and for assessing the efficacy of a variety of antimicrobial drugs. Positive correlations between the virulence of microbial pathogens in insects and mammals [4,5] have been established and the use of insects for screening microbial mutants or antimicrobial drugs is now recognized as a valuable approach to reduce the need to use mammals for this type of testing [6].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Drosophila S2 cells have been established as a suitable host model for bacterial infections (11)(12)(13). These macrophage-like cells were shown to behave similarly to mammalian cells in in vitro infection assays using L. monocytogenes.…”
mentioning
confidence: 99%